Changes of coat cover in primitive horses living on a reserve - Stachurska, A.; Robovský, Jan; Bocian, K.; Janczarek, I. (American Society of Animal Science, 2015)
Changes in the coat cover are important for mammalian thermoregulation. This is especially true where variable environmental conditions exist throughout the seasons. Coat cover shedding is the replacement of old coat hair with new hair. The process differs in various equids. The aim of the study was to examine the changes in the coat of primitive Polish Konik horses living on a reserve in southeast Poland (50.6319° N). The reserve is located in a temperate climate. The mean temperature is below 0°C in winter (December 8 to March 9) and over 15°C in summer (June 8 to September 8). Five adult mares were included in the study. The study used a specific methodical approach to quantitatively assess coat cover changes. Photos were taken once every 2 wk throughout the whole year to document the state of the mares’ coat. MultiScanBase software was used to analyze 260 photos. The percentage of the skin surface covered with short hair in relation to the surface of the body (without the head, neck, and limbs; short hair body [SHB]) was determined. To assess the topography of coat changes, surface parts covered with short hair within 6 regions of the body (shoulder, back, chest, loins, belly, and hindquarters; short hair part [SHP]) were considered separately.
Keywords: coat cover; hair; horse; season; shedding